A continuum damage mechanics-based unified creep and plasticity model for solder materials. (15th January 2015) - Yao, Yao; He, Xu; Keer, Leon M.; Fine, Morris E.
Abstract: A nonlinear continuum damage mechanics model is developed for both lead-rich and lead-free solder materials. A unified creep–plasticity constitutive relationship is adopted to simulate the inelastic behaviors; both isotropic and nonlinear kinematic hardening are considered. A traditional continuum damage evolution law is a function of actual damage parameter and effective accumulated plastic strain. In the current work, absolute temperature is introduced into the damage model to reflect the effect of temperature on the accumulated damage mechanism. The mechanical properties of solders, incorporating damage initiation and accumulation, were analyzed based on the model developed. Fatigue life under fully reversed cycling is investigated by monitoring the change in peak stresses, which decreases continuously, owing to damage accumulation. The numerical results were compared with experimental data. It was shown that the developed model can predict the whole damage accumulation process of different solder materials with reasonable accuracy.